The Relevance of Learning Arabic Qur'ani during the Covid-19 Pandemic and the Experience of Worship - Muhamad Fahri; Fajar Pinastia Arrahman; Muhammad Rizal Mahfujo (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
In addition to generating a health catastrophe, the Covid-19 epidemic altered the educational landscape from face-to-face instruction to online learning. University-based online learning also raises stress levels and student enrollment levels. As a result, it appears as though learning is less effective and does not immediately help pupils react to pandemic circumstances. The goal of this study is to determine if Qur'anic Arabic education online may enhance students' worship experiences as well as their Arabic language proficiency. By using a quantitative paradigm and analytical methods including the Paired Sample t-test, Confirmatory Factor Analysis, and Descriptive Analysis, This study demonstrates that online Qur'anic Arabic instruction is efficient in raising students' Arabic proficiency and offers the worship experience student tangible advantages.